Technological and Market related Capabilities and Competitiveness in the Brazilian Computer Industry: a case study (Revista Gestão & Conexões, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2013.2.2.4555.9-31The Brazilian local computer producers have the largest market share, even competing with large global players. This article objective is to discuss how the national private enterprises can compete in complex markets, accumulating not only technological competences but non technological ones. First, the technological paradigm theory allows dividing the computer industry in two groups: the enterprises that control the paradigm core and then push forward the technological frontier; and the enterprises whose competences encompass the secondary paradigm elements. Second, thePositivo’s analyses shows that this enterprise’s competitiveness isn’t connected to its technological competences. Also the elements that keep the local industry competitive are related to the population income expansion experienced in Brazil and due to the enterprise extreme specialization in the lower income population. It is concluded that the Brazilian computer industry can be competitive without accumulation technological competences.